Pengaruh Pengetahuan Terhadap Audit Judgement dengan Kompleksitas Tugas dan Independensi Sebagai Variabel Moderating (Studi Pada Akuntan Publik di KAP Wilayah Sumatera) - Febrianti, Irma; Sari, Ria Nelly; Darlis, Edfan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to examine the effect of auditors knowledge on the audit judgement with the complexity of the task and independency as a moderating variable. The population of this study were auditors who worked in Public Accountant Office in Sumatera region. This study used purposive sampling method and used SPSS 20 software to analize the data. The results prove that knowledge of auditor affect the audit judgement. This study also found that the interaction between complexity of the task and knowledge and the interaction between independency and knowledge have an effect on the auditor's judgment. The magnitude of the effect (R2) of the auditor knowledge, complexity of the task and independency on the audit judgement was 77%. While the remaining 23% is influenced by other variables.Keywords: auditor’s knowledge, complexity of the task, independency, audit judgement.